User satisfaction in the use of available alternative formats among visually impaired users of Library for the Blind Division of the National Library - Cayabyab, Mark James G. (2006)
This research sought to find out which alternative format(Braille books, Talking books and Talking computers) available in Library for the Blind Division in The National Library is best suited for visually impaired users of the library, its perceived advantages and disadvantages by the users and the factors that influence their choice of alternative format.